Perlindungan Hukum Pelaku Tindak Pidana Pencurian yang Dilakukan oleh Anak Berdasarkan Undang Undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Anak : Studi Putusan Nomor 33/Pid. Sus-Anak/2018/PN Gns - Luthfi Abiyu Fasya (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
This study aims to analyze the legal protection for children who commit theft, as examined in Decision Number 33/Pid.Sus-Anak/2018/PN Gns, focusing on how such protection is provided under Law Number 11 of 2012 concerning the Juvenile Justice System and the consequences of the absence of legal protection in sentencing children for theft. Using a normative legal research method that emphasizes positive law in the form of legislation and secondary legal materials as the primary sources, this study employs a statutory and case approach. The findings indicate that the decision has not optimally provided legal protection for children, as it does not fully adhere to the principle of the best interests of the child or the principle that deprivation of liberty and criminal sanctions should be a last resort. Moreover, the rights of children as offenders are not fully upheld, including the right not to be separated from their parents against their will. Consequently, if a child is sentenced to imprisonment, their relationship with their parents is severed, potentially leading to significant psychological and social impacts.